Zinc Deficiency in a Parenteral Nutrition–Dependent Patient During a Parenteral Trace Element Product Shortage. (28th January 2014) - Franck, Andrew J.
Abstract : Parenteral nutrition product shortages are common and place vulnerable patients at risk for nutrient deficiencies. This case report describes a parenteral nutrition–dependent patient who was found to have zinc deficiency during a parenteral nutrition product shortage. The management of the patient's zinc deficiency is described.